Author and Style: Intellectualization of Victor Domontovych`s Artistic Discourse - Kononenko, Vitaly (Journal of Vasyl Stefanyk Precarpathian National University, 2022)
The article highlights the features of the idiostyle of Victor Domontovych, a writer of 1920s, a representative of modernist artistic discourse. The stylistic manner of the author's writing shows his intellectualism, principles of his extraordinary scientifically oriented linguistic thinking. V. Domontovych depicts artistic reality through the prism of the ontological clash of categories of rational and irrational, real and unreal, intellectual and primitive-bourgeois, sexual and asexual. Using the concepts of plausible and implausible, real and conditional, the author characterizes the psycho-behavioral stereotypes of his characters in order to comment and evaluate their actions and decisions; he often uses a descriptive and contemplative manner, and forms of logical conclusions; therefore, a symbiosis of scientific and fictional presentation is formed. Domontovych's texts are full of ironic and mocking intonations in order to expose spirituality, low culture, meanness; the author strongly condemns selfishness, callousness, dishonesty in the behavior of the characters; the sharpness of his critical vision is directed against the arrogance of the intelligentsia, unjustified rationalism, scientific-like thinking, and bourgeoisie. The intellectual novels of the writer can be considered as extended metaphorical constructions, integral figurative and symbolic structures, profound artistic worldview carriers, as well as systems of meaning mythologizing. The author’s usage of linguistic and stylistic means is not extensive; they are unusual in their associative-figurative aspect and intended for the domain of cognitively meaningful perception. The expressiveness of texts is achieved through an implicit coded word usage, there is space for the reader to think creatively as the texts rely on the conceptual interaction within the system Author-Text-Reader.